Guarantees in securities - Lama More, Héctor Enrique (2012)
This paper addresses the guarantees or security interest granted in legal relationships, in other words, in mandatory or credit related legal relationships in which two parties or persons are identified: the active party, who is called the creditor or holder of a credit right, and the passive party, known as the debtor or liable party. Hence, facing the possibility of the breach of a duty or obligation imposed or assumed by the debtor, the guarantee constitutes the hope that such an obligation will be met and that the creditor’s loan will be satisfied. In this regard, the personal and real guarantees acknowledged by our civil and commercial laws are analyzed.